(untitled) (Eurasian Journal of Humanities and Social Sciences, 2023)
It is known that through sports, positive emotions such as self-confidence and self-esteem are formed in children and young people. A large part of the research is devoted to adolescents and their perceived sports competence. According to the facts, there is a connection between adolescents and children, between playing sports and the formation of a sense of self-confidence. It is noteworthy that self-esteem decreases in the youngest group and the highest in early adolescence, mid-adolescence, and recovers slightly in late adolescence. Sport is important in the formation of self-confidence in them during the same adolescence. This article will discuss detailed information on the physical health and self-confidence development of children and young people through sports.